Turismo e dinâmica demográfica: reflexos da atividade turística no comportamento reprodutivo da mulher no município de Salinópolis, PA - FRANÇA, Dalva Lúcia de Souza (Universidade Federal do Pará, 2014)
The discussion of the relationship of mutual dependence between population and economic development is complex and reflects a theoretical and practical concern pretty old, which has attracted the attention of thinkers and researchers over time. The theoretical discussion involving the motivating factors of tourism are also demographic factors that have particular importance in determining the levels and patterns of fertility, or the means used to plan the tourist activity in one place, drive new productive standards, spurring new values, patterns of consumption and lifestyles, impacting the reproductive behavior of women living in the tourist place. Given these arguments, the goal of this dissertation is to analyze and explain how the changes generated by the development of tourism has affected the dynamics of the population, especially the levels and patterns of fertility of women residing in the municipality of Salinópolis (PA). The study of the general hypothesis that the socioeconomic and spatial reorganization of Salinópolis from the development of tourism promoted changes in their population dynamics, particularly in reproductive behavior of women from 1970. In view of these considerations, it has developed an interpretative study where the database used were the population census from 1970 to 2000 and counting the population of the IBGE 2007, data from the Municipal Secretary of Health of Salinópolis (SMSS) linked with Information System on Live Births (Sinasc) and empirical research that has developed through stratified random probability sampling. The results show that the tourist activity has not brought to Salinopolitan society significant improvements in education, professional skills and labour supply, factors that have particular importance in determining the levels and patterns of fertility, however, the tourist activity affected the reproductive behavior of women in two distinct moments. First with the prevalence of high fertility rates, given the culture of recovery of large family associated with the large contingent of immigrant women of childbearing age in the municipality; a second time, the sharp fall in fertility before the messages of modernity brought by the tourist activity, growth of urban space and, mainly, by the action of public policies with regard to controlling the birth rate. However, the search results characterize the prevalence of high rates of fertility in Salinópolis, as in the state of Pará and the North region, when compared with nationally. In this context, the demographic implications generated by tourism in Salinópolis require the development of diagnostics sector and appropriate public policies.